Feasibility Study of Web-Based Application Pronalin as an Educational Media to Prevent Complications in Pregnant Women - Lestari, Meti Widiya; Budiarti, Yati; Herliani, Yulia; Astriyani, Endang; Kurniawati, Meti (Poltekkes Kemenkes Palu, 2024)
Introduction: The percentage of obstetric complication handling in Indonesia in 2018 reached 94.16%, West Java reached 91.7% and Tasikmalaya reached 116.9%. Data from the Puspahiang Health Center shows that 90 pregnant women experience complications. Efforts to minimize the incidence of complications in pregnant women can be made through the utilization of the birth planning and complication prevention (P4K) program through education based on the pronalin web-based application. Objective: This study aims to analyze the feasibility of the Pronalin Web-based application as a P4K education media for pregnant women. Method: This study uses the research and development (R&D) method, which passes material testing and application feasibility testing. Results: The validation assessment by material experts showed a score of 53 (feasible) and the results of the suitability test for use by pregnant women obtained a percentage of 79.4%, which means that the pronalin web-based application is